A solar photo-thermochemical hybrid system using peroxydisulfate for organic matters removal and improving ultrafiltration membrane performance in surface water treatment. (1st January 2021) - Guo, Yuanqing; Liang, Heng; Li, Guibai; Xu, Daliang; Yan, Zhongsen; Chen, Rui; Zhao, Jing; Tang, Xiaobin
Highlights: The solar-activated peroxydisulfate was adopted as a pretreatment prior to ultrafiltration. Solar light and heating effects played different roles in degrading NOMs at different temperatures. Terrestrially derived humic-like matters were the main cause of total membrane fouling. Irreversible membrane fouling was mainly attributed to protein-like substances. UV254 can be used for elevating membrane fouling control strategies to avoid excessive treatment. Abstract: Solar energy is considered one of the most promising energy sources for the degradation of pollutants in the water treatments. An innovative solar photo-thermochemical system involving peroxydisulfate (PDS) as an oxidant and xenon lamp as a solar irradiation light source was applied with hopes to degrade organic matters and alleviate the ultrafiltration (UF) membrane fouling when treating the real surface water. Moreover, heat-activated PDS pretreatment was used as a comparison to explore the respective proportions of solar light and heating effects, finding that solar light effect dominated the activation of PDS to degrade natural organic matters (NOMs) when the reaction temperature was below 50 °C and they both contributed to the production of free radicals at the temperature of >50 °C. The results indicated that solar-activated PDS pretreatment significantly alleviated membrane fouling caused by Songhua River water with the highest transmembrane pressure (TMP) reduction of approximately 69.6% at 70 °C. Organic substances (characterized by DOC, UV254 and the maximum florescent intensity) and micropollutant (atrazine) in the feed water were better degraded in the presence of solar light. Both total fouling index (TFI) and hydraulic irreversible fouling index (HIFI) were moderate correlated with the UV254 and DOC, whereas remarkably correlated with the Fmax of component 2 (C2) and component 3 (C3). In addition, no significant correlation was observed between fouling indexes (TFI and HIFI) and the Fmax of component 1 (C1). The membrane irreversible fouling was attributed to the accumulation of cake layers mainly composed of protein-like substances on the membrane surface. Solar-activated PDS pretreatment would efficiently degrade the protein-like substances and terrestrially derived humic-like matters to control UF membrane fouling. The findings are beneficial to develop new strategies for membrane fouling alleviation based on the solar irradiation and PDS oxidation. Graphical abstract: Image, graphical abstract